A novel low-cost capacitance-based approach for non-destructive evaluation of powder quality for food processing industries - Hari Krishna Salila Vijayalal Mohan; Andrew Alexander Malcolm (Measurement: Sensors, 2022)
In a high-volume food production line, several stainless-steel hoppers store, mix and dispense powdered ingredients to form food powders of the desired composition. Improper mixing at high speeds and caking (formation of lumps) during storage hamper powder homogeneity and quality. Currently, low throughput offline techniques such as spectroscopic analysis and powder flow tests are used to screen for powder mixing uniformity and caking. Herein, a flexible electrode system is proposed to detect capacitance changes based on the dielectric differences between different powders (beverage powders and their mixtures) and their subsequent variation from poor mixing/caking. The detection scheme successfully differentiated different powder mixtures and detected caking in powders non-invasively with good detection speed (50 ms) and low detection limits (15% for powder mixing and 1–43% for powder caking). Furthermore, the capacitive system integrated with an industrial food hopper successfully showcased an in-situ automated detection of powder caking.